2017
DOI: 10.1101/204529
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Auditory Motion Does Not Modulate Spiking Activity in the Middle Temporal and Medial Superior Temporal Visual Areas

Abstract: The integration of multiple sensory modalities is one of the key aspects of brain function, allowing animals to take advantage of concurrent sources of information to make more accurate perceptual judgments. For many years, it was thought that multisensory integration in the cerebral cortex only occurs in high-level "polysensory" association areas, but recent studies have demonstrated cross-modal influences in regions that were traditionally designated as unimodal. In particular, several human neuroimaging stu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 141 publications
0
2
0
Order By: Relevance
“…This would suggest that regions typically considered as purely unisensory may in fact show some level of abstraction by implementing canonical perceptual computations across the senses [16][17][18]. However, the idea that hMT + /V5 involves in motion processing other than for vision remains controversial and has notably been challenged by studies suggesting that the overlap between brain activity elicited by visual and non-visual motion is an artifactual byproduct of smoothing fMRI activity maps or by using group-level rather than individually defined hMT + /V5 [8,[10][11][12][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…This would suggest that regions typically considered as purely unisensory may in fact show some level of abstraction by implementing canonical perceptual computations across the senses [16][17][18]. However, the idea that hMT + /V5 involves in motion processing other than for vision remains controversial and has notably been challenged by studies suggesting that the overlap between brain activity elicited by visual and non-visual motion is an artifactual byproduct of smoothing fMRI activity maps or by using group-level rather than individually defined hMT + /V5 [8,[10][11][12][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that hMT+ may be inherently multisensory, capable of representing auditory as well as visual motion signals [82]. However, auditory motion does not modulate spiking responses in marmoset MT/MST [83], and the majority of studies have failed to find auditory BOLD responses within individually localized hMT+ in sighted individuals [64,75,84] (although auditory motion responses are found in a nearby region [75]). One recent study did show successful classification of up–down versus left–right auditory motion in hMT+ in sighted individuals [85].…”
Section: The Neural Basis Of Auditory Motion Processing In Early Blin...mentioning
confidence: 99%